(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
Continuous professional practice of students in higher education institutions plays an important role in improving their professional training and preparing them for the labor market. Internships provide an opportunity for students to turn theoretical knowledge into practical skills. This article examines the current state of managing the processes of organizing and conducting continuous professional practice of students on the example of foreign experiences.